Job Satisfaction of Nurses in Songklanagarind Hospital - Kraiwong, Nittaya; Leenum, Ratana (Princess of Naradhiwas University Journal, 2020)
This descriptive study aimed to evaluate the level of job satisfaction of nurses and its influential factors on job satisfaction. The samples were 1,129 professional nurses. Content validity index (CVI.) of questionnaires was judged by three experts at 1. The reliability was tested using Cronbach’s alpha coefficient yielding a value of 0.96. Questionnaires on job satisfaction was 6 aspects. The data analysis were frequency, percentage, mean and standard deviation. The association between influential factors and job satisfaction was tested by chi-square test. The results found that overall score for job satisfaction of nurses with high level (3.87 ± 0.36). The job characteristics gave the highest score of job satisfaction (4.11±0.42) and the compensation and employee welfare gave the lowest score job satisfaction (3.57±0.70). Three aspects which gave the highest job satisfaction score were 1) helpfulness of job (4.59±0.52), 2) good relationship with coworkers (4.15±0.57), and 3) educational possibilities (4.01±0.74). These aspects were significant different at P<0.01 in ward type, current position and the highest level of education.